Correlation of secondary salinization and soil conditioning in vegetable production under irrigation with saline water - Rivera-García, Arzu; Tuba, Géza; Kovács, Györgyi; Sinka, Lúcia; Zsembeli, József (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
Secondary salinization is a main problem around the world due to climate change and intrusion of salts in the soil by improper irrigation. Our aim was to study the soil salinization process by simulating vegetable production under irrigation with saline water (total soluble salt content ⁓700 mg L-1). We tested 6 different technologies of soil conditioner application and 3 vegetable crops with different sensitivity to salinity in a small plot experiment set up on a meadow chernozem soil. During the irrigation season in 2020, we regularly measured the electric conductivity (ECa) and the soil moisture content (v/v%) in the topsoil (0.1 m) and analysed these parameters with Pearson’s bivariate correlation method. As our hypothesis, we expected that there is correlation (PCC) among ECa, soil moisture content, soil conditioning, and providing the possibility to quantify the secondary salinization process. We found that all the 4 biosynthetic soil conditioners technologies minimized the harmful effect of saline irrigation. In the case of the not salt tolerant (NT) peas, the PCC correlation was higher to compost application and control expressing more intense salinization. NT beans showed a weaker correlation with lower PCCs, which must be due to its higher root activity leading to intensive leaching resulting in a lower degree of salinization. In the case of chilli with low salt tolerance (LT), micro dosing of soil conditioners was not effective in mitigating the harmful effect of secondary salinization, only full doses decreased the PCC. The salt tolerance of the investigated vegetable crops was also manifested in the yields. We found that PCC is a suitable statistical method to understand and quantify the process of secondary salinization.
Keywords: electric conductivity; soil moisture content; soil conditioners; salt tolerance; secondary salinization